2016
DOI: 10.26719/2016.22.6.368
|View full text |Cite
|
Sign up to set email alerts
|

Deaths of children aged under 5 years and realted factors in the Islamic Republic of Iran: a population-based case-control study

Abstract: The study was conducted to determine the family, social and economic factors associated with deaths of children aged under 5 years. A registry-based nested case-control study was conducted of the deaths of all children aged under 5 years in Kohgilooyeh and Boyer-Ahmad Province in the Islamic Republic of Iran. For each death, two controls were randomly selected among children of the same age, sex and place of residence (186 cases and 372 controls). Congenital abnormality (37.6%) and preterm birth (29.0%) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Anthropometric measures during early life and childhood are among the most useful parameters for assessing children's health (1,2) . In particular, weight and height are most widely used to assess many aspects of children's health and nutritional status (2,3) . Growth indices are associated with the risk of morbidity, mortality, and cognitive and even behavioural status (2,(4)(5)(6)(7) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Anthropometric measures during early life and childhood are among the most useful parameters for assessing children's health (1,2) . In particular, weight and height are most widely used to assess many aspects of children's health and nutritional status (2,3) . Growth indices are associated with the risk of morbidity, mortality, and cognitive and even behavioural status (2,(4)(5)(6)(7) .…”
mentioning
confidence: 99%
“…Anthropometric measures during early life and childhood are among the most useful parameters for assessing children’s health ( 1 , 2 ) . In particular, weight and height are most widely used to assess many aspects of children’s health and nutritional status ( 2 , 3 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-abused counterparts, women who experienced p-IPV are more likely to report a miscarriage (Fanslow et al, 2008), foetal injury due to physical violence (Kanawaku et al, 2015), LBW (Berhanie et al, 2019), growth delay of foetus (Nejatizade et al, 2017) small for gestational age (Alhusen et al, 2013), prematurity (Kiely et al, 2011), or preterm birth due to psychological abuse (Evazpoor et al, 2016;Hill et al, 2016;Nongrum et al, 2014;Rao et al, 2016). A recent case-control study in 2019 found that women who suffered p-IPV had a 3.1-fold increased probability of giving birth to an infant categorised as LBW and PTB (Alhusen et al, 2014;Berhanie et al, 2019).…”
Section: Reproductive Health Problems and Birth Outcomesmentioning
confidence: 99%
“…Breastfeeding has many advantages for both infants and mothers [5, 6]. The nutritional value of human milk is important for strengthening the infant’s immune system and protecting them against various infections, including diarrheic diseases and respiratory infections [7, 8].…”
Section: Introductionmentioning
confidence: 99%